Stretchable organic optoelectronic sensorimotor synapse - Lee, Yeongjun; Oh, Jin Young; Xu, Wentao; Kim, Onnuri; Kim, Taeho Roy; Kang, Jiheong; Kim, Yeongin; Son, Donghee; Tok, Jeffery B.-H.; Park, Moon Jeong; Bao, Zhenan; Lee, Tae-Woo (Science advances, 2018)
We developed a stretchable organic optoelectronic sensorimotor synapse to mimic a biological optical sensory nervous system. Emulation of human sensory and motor functions becomes a core technology in bioinspired electronics for next-generation electronic prosthetics and neurologically inspired robotics. An electronic synapse functionalized with an artificial sensory receptor and an artificial motor unit can be a fundamental element of bioinspired soft electronics. Here, we report an organic optoelectronic sensorimotor synapse that uses an organic optoelectronic synapse and a neuromuscular system based on a stretchable organic nanowire synaptic transistor (s-ONWST). The voltage pulses of a self-powered photodetector triggered by optical signals drive the s-ONWST, and resultant informative synaptic outputs are used not only for optical wireless communication of human-machine interfaces but also for light-interactive actuation of an artificial muscle actuator in the same way that a biological muscle fiber contracts. Our organic optoelectronic sensorimotor synapse suggests a promising strategy toward developing bioinspired soft electronics, neurologically inspired robotics, and electronic prostheses.